Identification of Food Sources of Apis cerana Fabricius, 1793 Based on Pollen Analysis - Moh Syahrial Farawansyah; Lestari MP Alibasyah; Manap Trianto; Masrianih Masrianih; Yulia Windarsih; Amalia Buntu (Biology, Medicine, & Natural Product Chemistry, 2026)
Apis cerana commonly known as the “Asian honey bee,” has been utilized for thousands of years across Asia, its native region, for honey production and pollination services. This species is often described as the closest “twin” of its European/African sister species, A. mellifera. This study aimed to identify plant species serving as pollen food sources for the honey bee A. cerana based on pollen morphological analysis. The research was conducted using a descriptive exploratory approach in Jononunu Village, Parigi Tengah District, Parigi Moutong Regency, Central Sulawesi, Indonesia. Pollen samples were collected from worker bees during foraging activities and subsequently analyzed through acetolysis and microscopic examination in the laboratory. Pollen identification was based on morphological characteristics, including exine ornamentation, aperture type, and pollen size.The results showed that A. cerana utilized pollen sources from 14 plant species belonging to 12 families, indicating a high diversity of forage resources. The identified pollen morphological characteristics comprised four types of exine ornamentation, six aperture types, and pollen sizes ranging from very small to large, with small- to medium-sized pollen being dominant. Tricolporate aperture types and psilate ornamentation were the most frequently observed characteristics. Based on plant growth form, pollen sources were predominantly derived from tree species, followed by herbs, while shrubs and bushes contributed less. These findings provide important baseline information for melissopalynological studies and may serve as a reference for the management and conservation of A. cerana and its forage plants.